Precise Temperature Measurement for Increasing the Survival of Newborn Babies in Incubator Environments - Frischer, Robert; Penhaker, Marek; Krejcar, Ondrej; Kacerovsky, Marian; Selamat, Ali (Sensors (Basel, Switzerland), 2014)
Precise temperature measurement is essential in a wide range of applications in the medical environment, however the regarding the problem of temperature measurement inside a simple incubator, neither a simple nor a low cost solution have been proposed yet. Given that standard temperature sensors don't satisfy the necessary expectations, the problem is not measuring temperature, but rather achieving the desired sensitivity. In response, this paper introduces a novel hardware design as well as the implementation that increases measurement sensitivity in defined temperature intervals at low cost.